(untitled) (Research, Society and Development, 2020)
Homeopathic products are one of the main alternatives to allopathic products, having several commercial products for veterinary use available on the market for different purposes. Therefore, the objective was to evaluate the zootechnical performance, egg quality and ectoparasites (lice) count in laying hens with advanced ages. The experiment was carried out at the Federal Institute of Triângulo Mineiro - Uberaba campus, using 90 birds of the commercial Delkalb® lineage, aged 89 to 93 weeks, distributed in a completely randomized design, divided into three treatments with five replications containing 6 birds per repetition totaling 30 birds per treatment. The treatments used consisted of: treatment 1 - without using the homeopathic product; treatment 2 - 1.0 g/bird/day of the homeopathic additive, treatment 3 - 1.5 g/bird/day of the homeopathic additive. No statistical difference was observed regarding the zootechnical performance and egg quality, however the percentage of laying of the birds were in expected values for the age of the birds, as for the egg quality, it can be observed that the Haugh unit was well below the values found in literature. The ectoparasite counts were not statistically influenced using the homeopathic product, this effect can be explained due to the high rate of lice infestation that affected the birds. It was concluded that the homeopathic product used was not efficient in controlling the infestation of ectoparasites (lice) present in birds, however it did not have any adverse effects on zootechnical performance or egg quality.